HUBUNGAN PENGETAHUAN IBU TENTANG ASUPAN GIZI 1000 HARI PERTAMA KEHIDUPAN DENGAN TUMBUH KEMBANG ANAK - Halimah Tusya Diah Harahap; Rani Darma Sakti Tanjung; Fitriyani Nasution (Jurnal Keperawatan Priority, 2023)
The first thousand days of life is a golden period or what is known as Golden Age for a child to grow and develop optimally. Brain growth is very rapid during this period, which can determine the quality of life of children in the future. Nutritional behavior is very important because it is a direct cause of nutritional problems in Indonesia Indonesia. However, any interruption during this period will impact the continuity of life and development of children. To find out the relation of a mother's behavior about 1000 days of the first life with the nutritional status of a toddler at the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency. This research is an analytic survey with a cross-sectional approach. The study’s population was all mothers with children aged 0-24 months, totaling 40 people. The sampling technique in this study used the total population technique. After the statistical test (Chi-Square) was carried out, it was found that there was a relationship between the mother's knowledge and a value of p = 0.010 (p <0.05) and there was a relationship between the mother's attitude and a value of p = 0.011 (p <0.05) about the first 1000 days of life and the growth and development of children at the Puskesmas. Sigambal. Exist The relationship between mother's knowledge and attitudes about the first 1000 days of life with child growth and development at the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency. nutritional status.